Benchmarking and calibrating FVS diameter growth predictions with tree-rings and forest inventory data in Sierra Nevada mixed-conifer forests - Eugenia K.L. Batista; Joseph D. Birch; Matthew Dickinson; Chad M. Hoffman; James A. Lutz; Andrew J. Larson; Jessica R. Miesel (Forest Ecology and Management, 2026)

North American crayfish: A quest for the biggest catch - Caitlin C. Bloomer; Susan B. Adams; Zanethia C. Barnett; Zackary A. Graham; Emmy M. Delekta; David M. Hayes; Zachary J. Loughman; Hugh MacIntosh; M. Worth Pugh; Karen Reed; Nathaniel F. Shoobs; Christopher A. Taylor; et al. (Ecology, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Nutrition Messaging in Food Documentaries: Assessment of Social Cognitive Theory Constructs and Information Quality - Enid A. Keseko; Minji Kim; Leila M. Larson; Amanda J. Fairchild; Alexis Bell; Gabrielle M. Turner-McGrievy (Journal of Nutrition Education and Behavior, 2026)

Genetic and ecological evidence for cryptic divergence within a species complex of rockfish in the Eastern Pacific - Anita Wray; R. N. Lou; G. Longo; W. Larson; P. H. Sudmant; J. Benante; J. H. Harms; J. R. Hyde; K. M. Nichols (Conservation Genetics, 2026)

Multiple Eurasian Origins and Admixture Shaped the Genomic Legacy of the House Mouse Invasion in Africa - Daniel Poveda‐Martinez; Philippe Gauthier; Margaux J. M. Lefebvre; Fanny Degrugillier; Gauthier Dobigny; Jean‐Pierre Quéré; Ambroise Dalecky; Youssoupha Niang; Mamadou Kane; Clark Mbou‐Boutambe; Joa Mangombi; Solimane Ag Atteynine; et al. (Molecular Ecology, 2026)
Commensal mammals offer unique opportunities to study how human‐mediated dispersal, admixture, and secondary contact shape genomic variation during range expansion, yet for one of the most successful invasive commensals globally, the western house mouse Mus musculus domesticus , invasion dynamics across Africa remain largely unexplored. Here, we present a large‐scale population genomic analysis of 380 whole‐genome sequences, including 303 newly sequenced low‐coverage genomes, of which 216 are from 13 distinct African populations, enabling us to investigate how human‐mediated dispersal and secondary contact with native species shape the genomic legacy of a commensal mammal invasion. Ancestry analyses reveal contributions from at least three major Eurasian source lineages contributing to African populations: an Iberian–West Asian lineage present in Morocco, Algeria, and Niger; a Mediterranean lineage represented in Tunisia; and a Northern European lineage dominant in West and Central Africa. Demographic inferences indicate both recent and ancient episodes of divergence and population contraction. In West and Central Africa, divergence times broadly overlap with European maritime expansion and colonial trade. In contrast, North African populations exhibit older coalescent signals, consistent with early participation in the western Mediterranean radiation. We also detect substantial introgression from the native Mus spretus into North African populations in regions of sympatry. Collectively, our results reveal that the African invasion of the house mouse was not a single demographic process but a mosaic of population‐specific histories shaped by multiple introductions, shifting connectivity through time, admixture, and interspecific gene flow. These findings reinforce the importance of population‐level perspectives in invasion genomics, especially for commensal mammals whose dispersal is closely tied to human movement, and establish the most extensive open genomic resource for wild African house mice.

The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Multi-media occurrence, bioaccumulation, and exposure assessment of PFAS across a Midwestern U.S. State - Maria S. Sepúlveda; Lisa Brown; Staci L. Capozzi; Samantha C. Cullom; Jeffrey E. Dick; Daniel J. Foti; Ronaldo H. Franjul; Nicole L. Franklin; Jennifer L. Freeman; Carolina Gonzalez-Canas; Wanyue Hui; Yuxin Jiang; et al. (Environmental Research, 2026)

Integrated Reanalysis of Global Riverine Fish eDNA Datasets Shows Robustness and Congruence of Biodiversity Conclusions - Yan Zhang; Heng Zhang; Hiroshi Akashi; Camille P. Albouy; Kara J. Andres; José Barquín; Jeanine Brantschen; Richard E. Connon; Joseph M. Craine; Deirdre Gleeson; Alejandra Goldenberg‐Vilar; Alexia M. González‐Ferreras; et al. (Molecular Ecology, 2026)
The analysis of environmental DNA (eDNA) has revolutionized biodiversity assessments in aquatic ecosystems, enabling non‐invasive monitoring of fish communities across diverse regions. However, the global comparability of these eDNA datasets remains ambiguous due to heterogeneous sampling protocols and bioinformatic workflows across studies, making it difficult to assess how robust and comparable the biodiversity patterns inferred from these datasets actually are. Here, we conducted a meta‐analysis of 58 riverine fish eDNA metabarcoding studies, covering 1818 sampling sites worldwide, to evaluate the robustness of eDNA‐derived biodiversity patterns. We found that species richness estimates and metrics of community structure derived under a common bioinformatic workflow were overall consistent with those of original analyses, despite the relatively high variability in bioinformatic analyses in the respective original studies. Contrastingly, congruence of species identity varied more extensively across datasets, mostly reflecting different completeness and regional relevance of reference databases. Restricting taxonomic assignment to basin‐specific species pools improved species identification accuracy, while datasets lacking publicly accessible or well‐curated reference data were more prone to mismatches. Year of sampling had a positive effect on taxonomic congruence, such that more recent studies showed increased robustness, also reflecting improved reference database coverage and enhanced species‐level identification over time and overall method congruence in more recent years. Overall, the suitability and potential of eDNA for global biodiversity monitoring is corroborating overall robust biodiversity estimates, irrespective of the bioinformatic approaches. Our study underlines the effectiveness and need for further harmonization of bioinformatic workflows and strengthened region‐specific reference databases for improved taxonomic resolution and comparability across studies.

Relationships among peri-traumatic circulating endocannabinoids and long-term, negative outcomes following traumatic injury - Emily A. Albertina; Carissa W. Tomas; Timothy J. Geier; Sydney C. Timmer-Murillo; Isela G. Pina; Kelley Jazinski-Chambers; Garrett Sauber; Jacklynn M. Fitzgerald; Christine L. Larson; Terri A. deRoon-Cassini; Cecilia J. Hillard (Psychopharmacology, 2026)
Rationale Traumatically injured individuals can develop chronic negative psychological sequelae. Improved understanding of contributing, peri-traumatic risk factors is essential to reduce the risk of these consequences. Previous studies have found that peri-traumatic, circulating endocannabinoid concentrations are positively associated with development of post-traumatic stress disorder (PTSD), chronic pain and depression months later, particularly in members of racial/ethnic groups that have been historically marginalized. Objectives This replication study examined relationships among peri-trauma serum endocannabinoid concentrations and long-term consequences in a cohort comprised primarily of individuals from marginalized racial and ethnic groups. Methods Participants ( n = 100; 81% from marginalized racial and ethnic groups) were traumatically injured adults presenting to the ED of an urban tertiary care hospital. Endocannabinoids N -arachidonoylethanolamine (AEA) and 2-arachidonoylglycerol (2-AG) were measured in serum collected within days (peri-trauma) and 6–10 months following injury (follow-up). Assessments, including PTSD, depression, pain and quality of life were completed. Statistical approaches, including multivariate, hierarchical regressions, were used to determine associations among serum endocannabinoid concentrations and long-term outcomes. Results Although it did not survive correction for multiple comparisons, peri-trauma serum 2-AG concentrations. Peri-trauma serum 2-AG concentrations were also positively associated with PTSD, pain severity, and functional engagement scores at follow-up. There were no significant associations between circulating 2-AG or AEA and depression. Conclusions These findings generally replicate earlier studies demonstrating that serum 2-AG concentrations are biomarkers of risk for PTSD and pain and uncover an additional association with poor functional quality of life. Further studies are needed to determine the underlying mechanisms of these relationships.

Pathways from socioeconomic values to natural resource management practices to ecological change: A systematic review - Bassie Yizengaw Limenih; Natalie Stoeckl; Silva Larson; Amber C.Y. Tsai; Vanessa M. Adams; Angela J. Dean (Biological Conservation, 2026)

Nonlinear thinking in ecology and evolution: applying the threshold elemental ratio across levels of ecological organization - Benjamin B. Tumolo; Carly R. Olson; Erin I. Larson; Halvor M. Halvorson; Catherine E. Wagner; Amy C. Krist; Felicia S. Osburn; Eric K. Moody; Linnea A. Rock; Uchechukwu V. C. Ogbenna; Eli N. Wess; Briante Najev; et al. (Oecologia, 2026)
Nonlinear dynamics govern ecological processes; thus, understanding thresholds is important for measuring and forecasting the effects of climate change and management of natural resources. However, identifying whether and how such thresholds transfer across ecological levels of organization remains challenging. We argue for a broadening of a foundational organismal concept from ecological stoichiometry theory, the threshold elemental ratio (TER), to study how nonlinear dynamics driven by shifts in limitation operate in evolutionary and ecological processes from organisms to ecosystems. Traditionally, TERs are used to describe the elemental ratio at which the limitation of organismal growth shifts from one element to another. Building on this definition, we make a case for broadening the TER beyond organisms to include populations, clades, communities, and ecosystems. We discuss how TERs may be detected and translated across different ecological levels and evolutionary processes through simulation modeling, literature review, and synthesis of empirical examples from diverse systems and scales including: cyanotoxin production in lakes, alder–salmon dynamics, and the Cambrian explosion. Collectively, we argue that TERs are likely widespread and consequential across levels of ecological organization and that such thresholds manifest from a diversity of mechanisms. Thus, applying the TER concept across ecological levels of organization holds promise for advancing our understanding of nonlinear dynamics from the micro-evolutionary to the macro-ecological.

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Significant mortality of old trees across a dry forest landscape, Oregon, USA - James D. Johnston; Paige N. Stephens; Micah R. Schmidt; Sean M.A. Jeronimo; Amanda E. Brackett; Amarina E. Wuenschel; Danielle E.M. Ulrich; Riley H. Paine; Lou F. Duloisy; Skye M. Greenler; Andrew J. Larson; Derek J. Churchill (Forest Ecology and Management, 2025)

Long-term exposure to extreme heat and cold and cognitive decline in older adults: Results from the Reasons for Geographic and Racial Differences in Stroke (REGARDS) cohort - Peter S. Larson; Phillipa Clarke; Robert Melendez; Jessica M. Finlay; Ketlyne Sol; Suzanne Judd; Iris Gomez-Lopez; Anam Khan; Carina J. Gronlund (Environmental Research, 2025)

Global Homogenisation of Plant Communities Along Mountain Roads by Non‐Native Species Despite Mixed Effects at Smaller Scales - Meike Buhaly; Jake M. Alexander; Aníbal Pauchard; Lisa J. Rew; Tim Seipel; José Ramón Arévalo; Valeria Aschero; Joshua P. Averett; Agustina Barros; Lohengrin A. Cavieres; V. Ralph Clark; Curtis C. Daehler; et al. (Global Ecology and Biogeography, 2025)
Aim Mountain ecosystems are experiencing increased invasion of non‐native plants. These increases in non‐native species put mountains at risk of biotic homogenisation and a reduction of biodiversity. Our study aims to test if non‐native plant species are contributing to biotic homogenisation along roadways in mountain regions and how this changes along elevation gradients and across spatial scales. Location 18 globally distributed mountain regions. Time Period 2012–2023. Major Taxa Studied Vascular plants. Methods We used standardised vegetation surveys including species cover from 18 mountain regions worldwide to analyse whether the addition of non‐native species to the native flora increased or decreased Bray–Curtis dissimilarity (i.e., beta‐diversity) among roadside plant communities along elevation gradients ranging from 15 to 3919 m a.s.l. We tested this at the local, regional, continental and global scales using mixed‐effects models and confirmed it using null models. Results In the New World, we mainly observed homogenisation across regions and scales, as beta‐diversity was mostly lower with the addition of non‐native species. This was particularly true for low elevations. In contrast, we predominantly found community differentiation in the Old World, specifically at smaller (i.e., local and regional) scales. At the global scale, communities became more similar through the addition of non‐native species at all elevations. Main Conclusions Large‐scale homogenisation might be interpreted as a signal that high‐elevation plant communities along roadways may become more similar as non‐native species continue to spread upwards. Future studies should investigate the mechanisms driving the observed patterns of both homogenisation and differentiation by non‐native species, and explore the potential consequences of these patterns for ecosystem function and resilience.

The Pragmatic Sceptic: A Practical Approach for Integrating Environmental DNA Into Marine Stock Assessment and Fisheries Management - Diana S. Baetscher; Kristen L. Omori; Daniel R. Goethel; Andrew Olaf Shelton; Aaron M. Berger; Kimberly J. Ledger; Krista M. Nichols; Wesley A. Larson (Fish and Fisheries, 2025)
The ‘omics revolution’ has advanced scientific understanding of marine ecosystems and led to a rapid increase in data that can inform species' population structure, distribution, and abundance. Of the 'omics data types, environmental DNA (eDNA) may present the most cost‐effective opportunity for developing quantitative estimates of abundance trends, a key input for stock assessment models. However, eDNA has yet to be widely adopted for stock status determinations within regional fisheries management organisations. We review progress towards addressing key challenges that limited the application of eDNA in marine fisheries management, including advances in (1) the quantitative relationship between eDNA observations and species biomass, (2) reducing false‐negative and false‐positive detections, (3) defining the spatial scale of eDNA, (4) collecting biological data from eDNA surveys, (5) quantifying uncertainty in eDNA surveys, and (6) responding to scepticism of new survey methods. We use a case study with Pacific hake ( Merluccius productus ) to demonstrate the development of an eDNA index and its direct integration into an age‐structured stock assessment model. Given the many ways in which the field of eDNA has matured, we propose that eDNA can meaningfully inform a range of fisheries management needs, and outline a roadmap for using eDNA in stock assessment models in data‐limited to data‐rich species. A primary impediment to operationalising eDNA as stock assessment model inputs is the lack of interdisciplinary research teams, including geneticists, ecological modellers, and stock assessment scientists, which are necessary to interpret methods and results across scientific disciplines and ensure data are used appropriately.

Pilot Trial of Nutri, a Digital Intervention for Personalized Dietary Management of Diabetes in Safety-Net Primary Care - Marissa Burgermaster; Madalyn Rosenthal; Brandon S. Altillo; Mariana Rendon Flores; Eesha Nayak; Dagny N. Larson; James Custer; Lola Okunade; William M. Tierney; Steven Andrews; Grant Daniels; Paul J. Rathouz (Journal of Nutrition Education and Behavior, 2025)

Pyrethroid insecticide pollution of wetlands reduces amphipod density - Breanna R. Keith; Danelle M. Larson; Carl W. Isaacson; Michael J. Anteau; Megan J. Fitzpatrick; Jake D. Carleen (Ecotoxicology, 2025)

Stimulant Use, HIV, and Plasma Metabolites Among Men - Emily M. Cherenack; Michaela E. Larson; Kevin Murray; Zachary J. Mayer; Candace Guerrero; Courtney A. Broedlow; Nichole R. Klatt; Adam W. Carrico (Journal of Neuroimmune Pharmacology, 2025)

Factors influencing landslide occurrence in low-relief formerly glaciated landscapes: landslide inventory and susceptibility analysis in Minnesota, USA - Laura D. Triplett; Morena N. Hammer; Stephen B. DeLong; Karen B. Gran; Carrie E. Jennings; Zachary T. Engle; Julie K. Bartley; Dylan J. Blumentritt; Andy J. Breckenridge; Stephanie Day; Melissa A. Kohout; Phil H. Larson; et al. (Natural Hazards, 2025)
In landscapes recently impacted by continental glaciation, landslides may occur where topographic relief has been generated by the drainage of glacial lakes and ensuing post-glacial fluvial network development into unconsolidated glacially derived sediments and exhumed bedrock. To investigate linkages among environmental variables, post-glacial landscape development, and landslides, we created a landslide inventory of nearly 10,000 landslides in five regions of the formerly glaciated low-relief state of Minnesota, United States. Multivariate logistic regression indicates the importance of slope angle, lithology, and the development of stream valleys to landslide distribution. Areas underlain by fine-grained glaciolacustrine and nearshore deposits that are incised by streams are particularly prone to shallow (< 1–2 m depth) landslides. Landslides also occur in a wide range of glacial and fluvial deposits, and as rockfall in layered Paleozoic sedimentary rocks in central and southern Minnesota and Precambrian igneous and sedimentary rocks in northeastern Minnesota. Although no more than 1–2% of the studied regions are susceptible to landslides, they can pose risk to life and safety, damage infrastructure, and impact water quality. The combination of recently generated low-relief steep slopes, extensive unconsolidated sediments, and layered sedimentary bedrock make this formerly glaciated landscape more susceptible to landslides than current national-scale models indicate.

Oral anti-endotoxin immunoglobulin Y (IgY) does not impact gut microbiome development in the first 28 days in foals - M. Mork; M.B. Conrad; A.M. Trauner; J. Hull; M. Hawkins; B. Robley; P. Larson; N. Pinkham; T. Wolfe; Q. Wang; S. Walk; A.N. Bradbery (Journal of Equine Veterinary Science, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Emotions and political identity predict public acceptance of urban deer management - Hannah M. Desrochers; M. Nils Peterson; Lincoln R. Larson; Christopher E. Moorman; Elizabeth M. Kierepka; John C. Kilgo; Nathan J. Hostetter (Urban Ecosystems, 2025)
Addressing public preferences can enhance wildlife management effectiveness and reduce backlash. We conducted novel research on public acceptance of wildlife management by accounting for the role of underexplored drivers including emotion and political identity across an urban-to-rural gradient. Using data from a 2022 survey about white-tailed deer ( Odocoileus virginianus ) in Durham County, North Carolina, we analyzed drivers of acceptance for three management strategies: passive management, lethal management by hunting, and lethal management by professionals. Support for deer management varied across the urban-to-rural gradient, as rural residents favored hunting but were less supportive of passive management compared to urban and suburban residents. Emotions and general attitudes toward deer were the strongest predictors of management acceptance. Support for passive management was higher among residents with more positive emotions toward deer, whereas support for lethal strategies was higher among those with more negative emotions. Additionally, political identity emerged as a complex yet influential factor in shaping support for lethal management. Conservative respondents exhibited a higher acceptance of hunting, whereas liberal respondents exhibited a higher acceptance of professional sharpshooting. Collectively, our results demonstrate the ways in which emotions, politics, and other socio-demographic factors interact to influence public support for deer management across the urban–rural gradient. When direct experience with wildlife is lacking (e.g., in urban areas), emotions may act as heuristic guides that shape preferences. Managers aiming to increase deer management acceptability could integrate insights about emotional, political, and demographic drivers of public management support in communication efforts, potentially rendering urban deer management more effective.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Patterns in tree squirrel co-occurrence vary with responses to local land cover in US cities - Rachel N. Larson; Heather A. Sander; Mason Fidino; Julia L. Angstmann; Sheryl Hayes Hursh; Seth B. Magle; Katrina Moore; Carmen M. Salsbury; Theodore Stankowich; Katherine Tombs; Lauren Barczak; Alyssa M. Davidge; et al. (Urban Ecosystems, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Fish Invasion of Prairie Pothole Wetlands Reduces Amphipod Abundance, A Key Vertebrate Forage - Jake D. Carleen; Danelle M. Larson; Michael J. Anteau; Megan J. Fitzpatrick; Andrew W. Hafs; Carl W. Isaacson; Breanna R. Keith (Wetlands, 2024)

Biodiversity in changing environments: An external‐driver internal‐topology framework to guide intervention - Katharine N. Suding; Courtney G. Collins; Lauren M. Hallett; Loralee Larios; Laurel M. Brigham; Joan Dudney; Emily C. Farrer; Julie E. Larson; Nancy Shackelford; Marko J. Spasojevic (Ecology, 2024)
Accompanying the climate crisis is the more enigmatic biodiversity crisis. Rapid reorganization of biodiversity due to global environmental change has defied prediction and tested the basic tenets of conservation and restoration. Conceptual and practical innovation is needed to support decision making in the face of these unprecedented shifts. Critical questions include: How can we generalize biodiversity change at the community level? When are systems able to reorganize and maintain integrity, and when does abiotic change result in collapse or restructuring? How does this understanding provide a template to guide when and how to intervene in conservation and restoration? To this end, we frame changes in community organization as the modulation of external abiotic drivers on the internal topology of species interactions, using plant–plant interactions in terrestrial communities as a starting point. We then explore how this framing can help translate available data on species abundance and trait distributions to corresponding decisions in management. Given the expectation that community response and reorganization are highly complex, the external‐driver internal‐topology (EDIT) framework offers a way to capture general patterns of biodiversity that can help guide resilience and adaptation in changing environments.

When is it safe to go home? Post-predation assessment of risk and safety when personal information conflicts with social cues - Brian D. Wisenden; Cat M. Adkins; Seth A. Campbell; Shree Chakraborty; Madelyn E. Cloutier; Alex D. Doebler; Kathryn A. Hanson; Lou Hoff; Molly I. M. Johnson; Philip S. Larson; Claire M. Lukasik; Zoe R. Michaelson; et al. (Behavioral Ecology and Sociobiology, 2024)

Benthic foraminifera in Gulf of Mexico show temporal and spatial dynamics of microplastics - Martina M. Plafcan; Patrick T. Schwing; Isabel C. Romero; Gregg R. Brooks; Rebekka A. Larson; Bryan J. O'Malley; Christopher D. Stallings (Marine Pollution Bulletin, 2024)

Using individual‐based trait frequency distributions to forecast plant‐pollinator network responses to environmental change - Aoife Cantwell‐Jones; Jason M. Tylianakis; Keith Larson; Richard J. Gill (Ecology Letters, 2024)
Determining how and why organisms interact is fundamental to understanding ecosystem responses to future environmental change. To assess the impact on plant‐pollinator interactions, recent studies have examined how the effects of environmental change on individual interactions accumulate to generate species‐level responses. Here, we review recent developments in using plant‐pollinator networks of interacting individuals along with their functional traits, where individuals are nested within species nodes. We highlight how these individual‐level, trait‐based networks connect intraspecific trait variation (as frequency distributions of multiple traits) with dynamic responses within plant‐pollinator communities. This approach can better explain interaction plasticity, and changes to interaction probabilities and network structure over spatiotemporal or other environmental gradients. We argue that only through appreciating such trait‐based interaction plasticity can we accurately forecast the potential vulnerability of interactions to future environmental change. We follow this with general guidance on how future studies can collect and analyse high‐resolution interaction and trait data, with the hope of improving predictions of future plant‐pollinator network responses for targeted and effective conservation.

Discussion: Prioritize perennial grain development for sustainable food production and environmental benefits - Lee R. DeHaan; James A. Anderson; Prabin Bajgain; Andrea Basche; Douglas J. Cattani; Jared Crain; Timothy E. Crews; Christophe David; Olivier Duchene; Jessica Gutknecht; Richard C. Hayes; Fengyi Hu; et al. (Science of The Total Environment, 2023)

A revised taxonomy and estimate of species diversity for western North American Lampetra - K. J. Carim; D. C. Larson; J. M. Helstab; M. K. Young; M. F. Docker (Environmental Biology of Fishes, 2023)
Lampreys are an ancient lineage of jawless fish for which the relationships among some lineages are uncertain. We addressed these information gaps for Lampetra species with a focus on western North America. Phylogenetic analysis using all publicly available sequences of two mitochondrial genes— cyt b and COI —supported designation of western North American Lampetra as a distinct genus from Lampetra in Europe, Asia, and eastern North America. Species delimitation analysis of cyt b sequences identified seven species, only three of which are currently recognized. Lampetra ayresii and L. richardsoni , regarded as separate under the “paired species concept,” were not genetically distinct; we recommend synonymizing L. richardsoni with L. ayresii because the latter has precedence, yet continuing to recognize each ecotype using its current common name. Other than the widespread L. ayresii clade, all other species exhibited limited ranges often restricted to one or two locations. Within headwaters of the Willamette River, L. ayresii demonstrated strong genetic structure and lack of gene flow among subbasins, indicating that the subbasin scale may represent an appropriate management unit. However, the appropriate management scale in other areas may differ based on evolutionary histories and gene flow. Subsequent work is needed across western North America to better delineate the ranges of the aforementioned species and to evaluate whether other unrecognized taxa in this lineage may be present.

Good Practices for the Laboratory Performance Testing of Aqueous Oral Inhaled Products (OIPs): an Assessment from the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) - Jolyon P. Mitchell; I. Carter; J. D. Christopher; M. Copley; W. H. Doub; A. Goodey; C. J. Gruenloh; B. B. Larson; S. Lyapustina; R. B. Patel; S. W. Stein; J. D. Suman (AAPS PharmSciTech, 2023)

Tree Mortality may Drive Landscape Formation: Comparative Study from Ten Temperate Forests - P. Šamonil; P. Daněk; J. A. Lutz; K. J. Anderson-Teixeira; J. Jaroš; J. D. Phillips; A. Rousová; D. Adam; A. J. Larson; J. Kašpar; D. Janik; I. Vašíčková; et al. (Ecosystems, 2023)

Differences in fouling community composition and space occupation across broad spatial and temporal scales - Elizabeth B. Jewett; Katherine N. Lawson; Kristen J. Larson; Brianna M. Tracy; Safra Altman; Andrew L. Chang; Scott Cowan; Jeffrey A. Crooks; Tamar Huber; Elizabeth H. Wells; Gregory M. Ruiz (Frontiers in Marine Science, 2022)
Sessile marine invertebrate (biofouling) communities have served as an important model in ecology for evaluating fundamental patterns and processes, including invasion dynamics, which vary at broad spatial and temporal scales. Here, we tested for differences in biofouling community development among three biogeographically distinct bays in North America (Chesapeake Bay, Tampa Bay, and San Francisco Bay), exploring possible explanations for differential non-native species success. In particular, we aimed to examine if San Francisco Bay (a global hotspot for non-native species richness) differed in composition and space occupation, especially since open space can facilitate colonization. Additionally, we explored how biogeography, assembly and succession dynamics over the short and long term, and space availability affect marine communities across broad spatial scales. Patterns of community assembly differed among bays, with more bare space and less secondary cover (species settling on species) in San Francisco Bay. San Francisco Bay was also distinguished by a higher percent cover of Tunicata (almost all of which are non-native and historically absent) over multiple time scales. Cirripedia recruited on bare panels in all three Bays but cover increased only in Tampa Bay, as soak time increased. Tube-dwelling Polychaeta distinguished Chesapeake Bay from Tampa Bay and San Francisco Bay. Low-salinity events temporarily restructured the communities in all three bays. Whether differences among bays reflect coastal versus bay-specific patterns remains to be tested.

Role of ocean dynamics in equatorial Pacific decadal variability - Yu Zhang; Shi-Yun Yu; Shang-Ping Xie; Dillon J. Amaya; Qihua Peng; Yu Kosaka; Xiaopei Lin; Jun-Chao Yang; Sarah M. Larson; Arthur J. Miller; Lei Fan (Climate Dynamics, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Functional localization of audiovisual speech using near infrared spectroscopy - Iliza M. Butera; Eric D. Larson; Andrea J. DeFreese; Adrian KC Lee; René H. Gifford; Mark T. Wallace (Brain Topography, 2022)
Visual cues are especially vital for hearing impaired individuals such as cochlear implant (CI) users to understand speech in noise. Functional Near Infrared Spectroscopy (fNIRS) is a light-based imaging technology that is ideally suited for measuring the brain activity of CI users due to its compatibility with both the ferromagnetic and electrical components of these implants. In a preliminary step toward better elucidating the behavioral and neural correlates of audiovisual (AV) speech integration in CI users, we designed a speech-in-noise task and measured the extent to which 24 normal hearing individuals could integrate the audio of spoken monosyllabic words with the corresponding visual signals of a female speaker. In our behavioral task, we found that audiovisual pairings provided average improvements of 103% and 197% over auditory-alone listening conditions in −6 and −9 dB signal-to-noise ratios consisting of multi-talker background noise. In an fNIRS task using similar stimuli, we measured activity during auditory-only listening, visual-only lipreading, and AV listening conditions. We identified cortical activity in all three conditions over regions of middle and superior temporal cortex typically associated with speech processing and audiovisual integration. In addition, three channels active during the lipreading condition showed uncorrected correlations associated with behavioral measures of audiovisual gain as well as with the McGurk effect. Further work focusing primarily on the regions of interest identified in this study could test how AV speech integration may differ for CI users who rely on this mechanism for daily communication.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Minimizing Ecological Impacts of Marine Energy Lighting - Caroline E. Reilly; Julia Larson; Alicia M. Amerson; Garrett J. Staines; Joseph H. Haxel; Paul Morgan Pattison (Journal of Marine Science and Engineering, 2022)
Marine energy is poised to become an important renewable energy contributor for the U.S., but widespread deployment of the technology hinges on its benefits outweighing the potential ecological impacts. One stressor marine energy installations introduce is light, which is known to cause varying responses among wildlife and has not yet been addressed as an environmental concern. This review discusses requirements and regulations for similar structures and how lighting design choices can be made to meet these requirements while minimizing environmental consequences. More practical guidance on implementing lighting for marine energy is needed, as well as updated guidelines to reflect technological and research advances. Known responses of wildlife to light are introduced in addition to how the responses of individuals may lead to ecosystem-level changes. The impact of light associated with marine energy installations can be reduced by following basic guidance provided herein, such as removing excess lighting, using lights with high directionality, and employing controls to reduce light levels. Continued research on animal responses to light, such as findings on minimum light levels for animal responses, alongside the development of highly-sensitivity spectral characterization capabilities can further inform lighting guidelines for deploying future open ocean marine energy devices.

High abundance of a single taxon (amphipods) predicts aquatic macrophyte biodiversity in prairie wetlands - Danelle M. Larson; Demey DeJong; Michael J. Anteau; Megan J. Fitzpatrick; Breanna Keith; Emily G. Schilling; Barry Thoele (Biodiversity and Conservation, 2022)
Conservation programs often aim to protect the abundance of individual species and biodiversity simultaneously. We quantified relations between amphipod densities and aquatic macrophyte (large plants and algae) diversity to test a hypothesis that biodiversity can support high abundance of a single taxonomic group. Amphipods ( Gammarus lacustris and Hyalella azteca ) are key forage for waterfowl and are declining in the Prairie Pothole Region of North America. We sampled a large gradient of amphipod densities (0–7050 amphipods/m 3 ) in 49 semi-permanent wetlands, and 50% of the study wetlands had high amphipod densities (> 500 amphipods/m 3 ). Generalized linear models revealed G. lacustris and H. azteca densities increased exponentially with macrophyte diversity indices. Further, H. azteca densities were greatest at moderate levels of submersed vegetation biomass. Community analyses showed both amphipod species were positively associated with diverse macrophyte assemblages and negatively associated with high coverage of cattails ( Typha spp.), a taxon that creates monotypic stands, as well as bladderwort ( Utricularia spp.), a carnivorous plant. Our results indicate that amphipods could be used as an umbrella species for protecting diverse macrophyte communities in semi-permanent and permanent wetlands of North America’s Prairie Pothole Region.

Timing and hydrological conditions associated with bigheaded carp movement past navigation dams on the upper Mississippi river - Jon M. Vallazza; Kyle J. Mosel; David M. Reineke; Ann L. Runstrom; James H. Larson; Brent C. Knights (Biological Invasions, 2021)

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Translocations maintain genetic diversity and increase connectivity in sea otters, Enhydra lutris - Shawn Larson; Roderick B. Gagne; Jim Bodkin; Michael J. Murray; Katherine Ralls; Lizabeth Bowen; Raphael Leblois; Sylvain Piry; Maria Cecilia Penedo; M. Tim Tinker; Holly B. Ernest (Marine Mammal Science, 2021)
Sea otters, Enhydra lutris , were once abundant along the nearshore areas of the North Pacific. The international maritime fur trade that ended in 1911 left 13 small remnant populations with low genetic diversity. Subsequent translocations into previously occupied habitat resulted in several reintroduced populations along the coast of North America. We sampled sea otters between 2008 and 2011 throughout much of their current range and used 19 nuclear microsatellite markers to evaluate genetic diversity, population structure, and connectivity between remnant and reintroduced populations. Average genetic diversity within populations was similar: observed heterozygosity 0.55 and 0.53, expected heterozygosity 0.56 and 0.52, unbiased expected heterozygosity 0.57 and 0.52, for reintroduced and remnant populations, respectively. Sea otter population structure was greatest between the Northern and Southern sea otters with further structuring in Northern sea otters into Western, Central, and Southeast populations (including the reintroduced populations). Migrant analyses suggest the successful reintroductions and growth of remnant groups have enhanced connectivity and gene flow between populations throughout many of the sampled Northern populations. We recommend that future management actions for the Southern sea otter focus on future reintroductions to fill the gap between the California and Washington populations ultimately restoring gene flow to the isolated California population.

The role of tumor heterogeneity in immune-tumor interactions - Shelby M. Knoche; Alaina C. Larson; Bailee H. Sliker; Brittany J. Poelaert; Joyce C. Solheim (Cancer and Metastasis Reviews, 2021)

The FamilyTalk randomized controlled trial: patient-reported outcomes in clinical genetic sequencing for colorectal cancer - Sukh Makhnoon; Deborah J. Bowen; Brian H. Shirts; Stephanie M. Fullerton; Eric B. Larson; James D. Ralston; Kathleen A. Leppig; David R. Crosslin; David Veenstra; Gail P. Jarvik (Cancer Causes & Control, 2021)

Who is abuzz about bees? Explaining residents’ attitudes in Phoenix, Arizona - Kelli L. Larson; Melissa Fleeger; Susannah B. Lerman; Megan M. Wheeler; Riley Andrade; Jeffrey A. Brown; Sharon J. Hall; Desiree L. Narango (Urban Ecosystems, 2021)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Evaluating Restoration Treatment Effectiveness through a Comparison of Residual Composition, Structure, and Spatial Pattern with Historical Reference Sites - Miles E LeFevre; Derek J Churchill; Andrew J Larson; Sean M A Jeronimo; Jamie Bass; Jerry F Franklin; Van R Kane (Forest Science, 2020)
Forest-restoration efforts are increasing in the western United States in response to realized and expected changes in climate and disturbance regimes. Managers are challenged to find practical and defensible targets to shift forest composition, structure, and spatial pattern to a more resistant and resilient state. The Northeast Washington Forest Vision 2020 project on the Colville National Forest presented an opportunity to map and use previously uncaptured mesic stand-level historical reference conditions to a large restoration project. We reconstructed historical forest conditions in 12 plots across a range of plant-association groups and mapped five restoration treatment units after implementation. We evaluated treatment effectiveness both in terms of meeting the prescriptions’ stated objectives and by similarity to observed reference conditions using metrics of density, species composition, clump-size patterns, and open-space patterns. We found that dry plant associations were historically dominated by distributed clumps of large shade-intolerant trees, whereas cold mesic plant associations were structured as a gap-matrix spatial pattern. Treatments were effective at meeting prescribed density and species-composition targets, but generally resulted in stands that were overly uniform or clumped compared to historical reference conditions.

Caveolin-1 regulates medium spiny neuron structural and functional plasticity - Katherine R. Tonn Eisinger; Andrew D. Chapp; Samuel P. Swanson; Daniel Tam; Natalie M. Lopresti; Erin B. Larson; Mark J. Thomas; Lorene M. Lanier; Paul G. Mermelstein (Psychopharmacology, 2020)

The impact of the extratropics on ENSO diversity and predictability - Kathy Pegion; Christopher M. Selman; Sarah Larson; Jason C. Furtado; Emily J. Becker (Climate Dynamics, 2020)

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

Fixing a snag in carbon emissions estimates from wildfires - Jeffrey E. Stenzel; Kristina J. Bartowitz; Melannie D. Hartman; James A. Lutz; Crystal A. Kolden; Alistair M. S. Smith; Beverly E. Law; Mark E. Swanson; Andrew J. Larson; William J. Parton; Tara W. Hudiburg (Global Change Biology, 2019)
Wildfire is an essential earth‐system process, impacting ecosystem processes and the carbon cycle. Forest fires are becoming more frequent and severe, yet gaps exist in the modeling of fire on vegetation and carbon dynamics. Strategies for reducing carbon dioxide (CO 2 ) emissions from wildfires include increasing tree harvest, largely based on the public assumption that fires burn live forests to the ground, despite observations indicating that less than 5% of mature tree biomass is actually consumed. This misconception is also reflected though excessive combustion of live trees in models. Here, we show that regional emissions estimates using widely implemented combustion coefficients are 59%–83% higher than emissions based on field observations. Using unique field datasets from before and after wildfires and an improved ecosystem model, we provide strong evidence that these large overestimates can be reduced by using realistic biomass combustion factors and by accurately quantifying biomass in standing dead trees that decompose over decades to centuries after fire (“snags”). Most model development focuses on area burned; our results reveal that accurately representing combustion is also essential for quantifying fire impacts on ecosystems. Using our improvements, we find that western US forest fires have emitted 851 ± 228 Tg CO 2 (~half of alternative estimates) over the last 17 years, which is minor compared to 16,200 Tg CO 2 from fossil fuels across the region.

Influence of occupation history and habitat on Washington sea otter diet - Jessica R. Hale; Kristin L. Laidre; M. Tim Tinker; Ronald J. Jameson; Steven J. Jeffries; Shawn E. Larson; James L. Bodkin (Marine Mammal Science, 2019)
Habitat characteristics are primary determinants of nearshore marine communities. However, biological drivers like predation can also be important for community composition. Sea otters ( Enhydra lutris ssp.) are a salient example of a keystone species exerting top‐down control on ecosystem community structure. The translocation and subsequent population growth and range expansion of the northern sea otter ( Enhydra lutris kenyoni ) in Washington State over the last five decades has created a spatio‐temporal gradient in sea otter occupation time and density, and acts as a natural experiment to quantify how sea otter population status and habitat type influence sea otter diet. We collected focal observations of sea otters foraging at sites across the gradient in varying habitat types between 2010 and 2017. We quantified sea otter diet composition and diversity, and long‐term rates of energy gain across the gradient. We found that sea otter diet diversity was positively correlated with cumulative sea otter density, while rate of energy gain was negatively correlated with cumulative density. Additionally, we found that habitat type explained 1.77 times more variance in sea otter diet composition than sea otter cumulative density. Long‐term diet studies can provide a broader picture of sea otter population status in Washington State.

Effects of optical sensing based variable rate nitrogen management on yields, nitrogen use and profitability for cotton - M. Stefanini; J. A. Larson; D. M. Lambert; X. Yin; C. N. Boyer; P. Scharf; B. S. Tubaña; J. J. Varco; D. Dunn; H. J. Savoy; M. J. Buschermohle (Precision Agriculture, 2019)

Real-Time Monitoring with a Tablet App Improves Implementation of Treatments to Enhance Forest Structural Diversity - Colin T Maher; Emily Oja; Abigail Marshall; Matthew Cunningham; Lucas Townsend; Graham Worley-Hood; Luke Ruffner Robinson; Taylor Margot; Drew Lyons; Stuart Fety; Eryn E Schneider; Sean M A Jeronimo; et al. (Journal of Forestry, 2019)

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Alien plants as mediators of ecosystem services and disservices in urban systems: a global review - Luke J. Potgieter; Mirijam Gaertner; Christoph Kueffer; Brendon M. H. Larson; Stuart W. Livingstone; Patrick J. O’Farrell; David M. Richardson (Biological Invasions, 2017)

Whole exome sequencing of wild-derived inbred strains of mice improves power to link phenotype and genotype - Peter L. Chang; Emily Kopania; Sara Keeble; Brice A. J. Sarver; Erica Larson; Annie Orth; Khalid Belkhir; Pierre Boursot; François Bonhomme; Jeffrey M. Good; Matthew D. Dean (Mammalian Genome, 2017)

Low back skin sensitivity has minimal impact on active lumbar spine proprioception and stability in healthy adults - Shawn M. Beaudette; Katelyn J. Larson; Dennis J. Larson; Stephen H. M. Brown (Experimental Brain Research, 2016)

Ecosystem services in managing residential landscapes: priorities, value dimensions, and cross-regional patterns - K. L. Larson; K. C. Nelson; S. R. Samples; S. J. Hall; N. Bettez; J. Cavender-Bares; P. M. Groffman; M. Grove; J. B. Heffernan; S. E. Hobbie; J. Learned; J. L. Morse; et al. (Urban Ecosystems, 2016)

Effect of field geometry on profitability of automatic section control for chemical application equipment - James A. Larson; Margarita M. Velandia; Michael J. Buschermohle; Shaun M. Westlund (Precision Agriculture, 2016)

Human activities cause distinct dissolved organic matter composition across freshwater ecosystems - Clayton J. Williams; Paul C. Frost; Ana M. Morales‐Williams; James H. Larson; William B. Richardson; Aisha S. Chiandet; Marguerite A. Xenopoulos (Global Change Biology, 2016)
Dissolved organic matter ( DOM ) composition in freshwater ecosystems is influenced by the interactions among physical, chemical, and biological processes that are controlled, at one level, by watershed landscape, hydrology, and their connections. Against this environmental template, humans may strongly influence DOM composition. Yet, we lack a comprehensive understanding of DOM composition variation across freshwater ecosystems differentially affected by human activity. Using optical properties, we described DOM variation across five ecosystem groups of the Laurentian Great Lakes region: large lakes, Kawartha Lakes, Experimental Lakes Area, urban stormwater ponds, and rivers ( n = 184 sites). We determined how between ecosystem variation in DOM composition related to watershed size, land use and cover, water quality measures (conductivity, dissolved organic carbon ( DOC ), nutrient concentration, chlorophyll a ), and human population density. The five freshwater ecosystem groups had distinctive DOM composition from each other. These significant differences were not explained completely through differences in watershed size nor spatial autocorrelation. Instead, multivariate partial least squares regression showed that DOM composition was related to differences in human impact across freshwater ecosystems. In particular, urban/developed watersheds with higher human population densities had a unique DOM composition with a clear anthropogenic influence that was distinct from DOM composition in natural land cover and/or agricultural watersheds. This nonagricultural, human developed impact on aquatic DOM was most evident through increased levels of a microbial, humic‐like parallel factor analysis component (C6). Lotic and lentic ecosystems with low human population densities had DOM compositions more typical of clear water to humic‐rich freshwater ecosystems but C6 was only present at trace to background levels. Consequently, humans are strongly altering the quality of DOM in waters nearby or flowing through highly populated areas, which may alter carbon cycles in anthropogenically disturbed ecosystems at broad scales.

Effects of age on arterial stiffness and central blood pressure after an acute bout of resistance exercise - Robert S. Thiebaud; Christopher A. Fahs; Lindy M. Rossow; Jeremy P. Loenneke; Daeyeol Kim; J. Grant Mouser; Travis W. Beck; Debra A. Bemben; Rebecca D. Larson; Michael G. Bemben (European Journal of Applied Physiology, 2016)

Factors affecting individual foraging specialization and temporal diet stability across the range of a large “generalist” apex predator - Adam E. Rosenblatt; James C. Nifong; Michael R. Heithaus; Frank J. Mazzotti; Michael S. Cherkiss; Brian M. Jeffery; Ruth M. Elsey; Rachel A. Decker; Brian R. Silliman; Louis J. Guillette; Russell H. Lowers; Justin C. Larson (Oecologia, 2015)

Multi-ethnic analysis reveals soluble l-selectin may be post-transcriptionally regulated by 3′UTR polymorphism: the Multi-Ethnic Study of Atherosclerosis (MESA) - Cecilia Berardi; Nicholas B. Larson; Paul A. Decker; Christina L. Wassel; Phillip S. Kirsch; James S. Pankow; Michele M. Sale; Mariza de Andrade; Hugues Sicotte; Weihong Tang; Naomi Q. Hanson; Michael Y. Tsai; et al. (Human Genetics, 2015)

Using geodetic GPS receivers to measure vegetation water content - Wei Wan; Kristine M. Larson; Eric E. Small; Clara C. Chew; John J. Braun (GPS Solutions, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Relationships Between Land Cover and Dissolved Organic Matter Change Along the River to Lake Transition - James H. Larson; Paul C. Frost; Marguerite A. Xenopoulos; Clayton J. Williams; Ana M. Morales-Williams; Jon M. Vallazza; John C. Nelson; William B. Richardson (Ecosystems, 2014)

Patterns of parasitoid host utilization and development across a range of temperatures: implications for biological control of an invasive forest pest - Jian J. Duan; David E. Jennings; Dontay C. Williams; Kristi M. Larson (BioControl, 2014)

Persistence and stability of Eastern Afromontane forests: evidence from brevicipitid frogs - Simon P. Loader; F. Sara Ceccarelli; Michele Menegon; Kim M. Howell; Roman Kassahun; Abebe A. Mengistu; Samy A. Saber; Fikirte Gebresenbet; Rafael de Sá; Tim R. B. Davenport; Joanna G. Larson; Hendrik Müller; et al. (Journal of Biogeography, 2014)
Aim The persistence and stability of habitats through time are considered predictors of high levels of biodiversity in some environments. Long‐term habitat persistence and stability may explain the species‐rich, endemic forest fauna and flora of the Eastern Afromontane Biodiversity Region ( EABR ). Using complementary phylogenetic and biogeographical approaches, we examine evolutionary patterns in EABR brevicipitid frogs. Using these data, we test whether brevicipitid history reflects patterns of long‐term forest persistence and/or stability across the EABR . Location East Africa. Methods A dated phylogeny for brevicipitids was constructed using two nuclear and three mitochondrial markers. Alternative diversification models were used to determine signal for constant or varying net diversification rates. Using our dated tree, we identified areas of high phylogenetic diversity ( PD ), and inferred ancestral areas using likelihood and Bayesian approaches. Results Brevicipitids have a long history, with generic diversification among extant lineages pre‐dating the Oligocene (> 33 Ma). Ancestral‐area reconstructions indicate the presence of brevicipitids in the EABR since the Oligocene, and support a scenario of palaeoendemics surviving in EABR refugia. Ancestral‐area reconstructions indicate that the central Eastern Arc Mountains ( EAM ) formed the initial centre of diversification of forest brevicipitids. Measures of PD show that diversity varies across the EABR but is highest in the EAM . Constant net diversification rate in brevicipitids is a significantly better fit than alternative, rate‐variable models. Main conclusions The degree of persistence of forest habitats appears to be a contributing factor to the varying levels of diversity across the EABR in brevicipitids (and other organisms). In contrast to the Southern Highlands and Ethiopian Bale Mountains, the EAM stands out as an area that enabled the constant accumulation of brevicipitid species over a long period of time.

Convergent Surface Water Distributions in U.S. Cities - M. K. Steele; J. B. Heffernan; N. Bettez; J. Cavender-Bares; P. M. Groffman; J. M. Grove; S. Hall; S. E. Hobbie; K. Larson; J. L. Morse; C. Neill; K. C. Nelson; et al. (Ecosystems, 2014)

Development and application of genomic tools to the restoration of green abalone in southern California - K. M. Gruenthal; D. A. Witting; T. Ford; M. J. Neuman; J. P. Williams; D. J. Pondella; A. Bird; N. Caruso; J. R. Hyde; L. W. Seeb; W. A. Larson (Conservation Genetics, 2014)

A genome- and phenome-wide association study to identify genetic variants influencing platelet count and volume and their pleiotropic effects - Khader Shameer; Joshua C. Denny; Keyue Ding; Hayan Jouni; David R. Crosslin; Mariza de Andrade; Christopher G. Chute; Peggy Peissig; Jennifer A. Pacheco; Rongling Li; Lisa Bastarache; Abel N. Kho; et al. (Human Genetics, 2014)

Community‐specific impacts of exotic earthworm invasions on soil carbon dynamics in a sandy temperate forest - Jasmine M. Crumsey; James M. Le Moine; Yvan Capowiez; Mitchell M. Goodsitt; Sandra C Larson; George W. Kling; Knute J. Nadelhoffer (Ecology, 2013)
Exotic earthworm introductions can alter above‐ and belowground properties of temperate forests, but the net impacts on forest soil carbon (C) dynamics are poorly understood. We used a mesocosm experiment to examine the impacts of earthworm species belonging to three different ecological groups ( Lumbricus terrestris [anecic], Aporrectodea trapezoides [endogeic], and Eisenia fetida [epigeic]) on C distributions and storage in reconstructed soil profiles from a sandy temperate forest soil by measuring CO 2 and dissolved organic carbon (DOC) losses, litter C incorporation into soil, and soil C storage with monospecific and species combinations as treatments. Soil CO 2 loss was 30% greater from the Endogeic × Epigeic treatment than from controls (no earthworms) over the first 45 days; CO 2 losses from monospecific treatments did not differ from controls. DOC losses were three orders of magnitude lower than CO 2 losses, and were similar across earthworm community treatments. Communities with the anecic species accelerated litter C mass loss by 31–39% with differential mass loss of litter types ( Acer rubrum > Populus grandidentata > Fagus grandifolia > Quercus rubra ≥ Pinus strobus ) indicative of leaf litter preference. Burrow system volume, continuity, and size distribution differed across earthworm treatments but did not affect cumulative CO 2 or DOC losses. However, burrow system structure controlled vertical C redistribution by mediating the contributions of leaf litter to A‐horizon C and N pools, as indicated by strong correlations between (1) subsurface vertical burrows made by anecic species, and accelerated leaf litter mass losses (with the exception of P. strobus ); and (2) dense burrow networks in the A‐horizon and the C and N properties of these pools. Final soil C storage was slightly lower in earthworm treatments, indicating that increased leaf litter C inputs into soil were more than offset by losses as CO 2 and DOC across earthworm community treatments.

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Population pharmacokinetic and exposure-response analysis of nilotinib in patients with newly diagnosed Ph+ chronic myeloid leukemia in chronic phase - Richard A. Larson; Ophelia Q. P. Yin; Andreas Hochhaus; Giuseppe Saglio; Richard E. Clark; Hirohisa Nakamae; Neil J. Gallagher; Eren Demirhan; Timothy P. Hughes; Hagop M. Kantarjian; Philipp D. le Coutre (European Journal of Clinical Pharmacology, 2012)

Genetic variants associated with the white blood cell count in 13,923 subjects in the eMERGE Network - David R. Crosslin; Andrew McDavid; Noah Weston; Sarah C. Nelson; Xiuwen Zheng; Eugene Hart; Mariza de Andrade; Iftikhar J. Kullo; Catherine A. McCarty; Kimberly F. Doheny; Elizabeth Pugh; Abel Kho; et al. (Human Genetics, 2012)

Residential landscapes as social-ecological systems: a synthesis of multi-scalar interactions between people and their home environment - Elizabeth M. Cook; Sharon J. Hall; Kelli L. Larson (Urban Ecosystems, 2012)

Evaluation of the Diurnal Cycle in the Atmospheric Boundary Layer Over Land as Represented by a Variety of Single-Column Models: The Second GABLS Experiment - G. Svensson; A. A. M. Holtslag; V. Kumar; T. Mauritsen; G. J. Steeneveld; W. M. Angevine; E. Bazile; A. Beljaars; E. I. F. de Bruijn; A. Cheng; L. Conangla; J. Cuxart; et al. (Boundary-Layer Meteorology, 2011)

Age-related changes in the corpus callosum in early-onset bipolar disorder assessed using volumetric and cross-sectional measurements - Melissa Lopez-Larson; Janis L. Breeze; David N. Kennedy; Steven M. Hodge; Lena Tang; Constance Moore; Anthony J. Giuliano; Nikos Makris; Verne S. Caviness; Jean A. Frazier (Brain Imaging and Behavior, 2010)

An Overview of Livestock-Associated MRSA in Agriculture - Abby L. Harper; Dwight D. Ferguson; Kerry R. Leedom Larson; Blake M. Hanson; Michael J. Male; Kelley J. Donham; Tara C. Smith (Journal of Agromedicine, 2010)

Species delimitation tests of endemic Lepidium papilliferum and identification of other possible evolutionarily significant units in the Lepidium montanum complex (Brassicaceae) of western North America - Steven R. Larson; C. M. Culumber; R. N. Schweigert; N. J. Chatterton (Conservation Genetics, 2010)

The NIFSTD and BIRNLex Vocabularies: Building Comprehensive Ontologies for Neuroscience - William J. Bug; Giorgio A. Ascoli; Jeffrey S. Grethe; Amarnath Gupta; Christine Fennema-Notestine; Angela R. Laird; Stephen D. Larson; Daniel Rubin; Gordon M. Shepherd; Jessica A. Turner; Maryann E. Martone (Neuroinformatics, 2008)

Localization of myosin-Va in subpopulations of cells in rat endocrine organs - Foued S. Espindola; Silmara R. Banzi; Luciana K. Calabria; Rodrigo J. Custódio; Ricardo A. Oliveira; Leandro D. Procópio; Andreia B. P. Lima; Jair P. Cunha-Junior; Milton V. Coelho; Iêda M. L. Guedes; Cláudia H. Pellizzon; Roy E. Larson; et al. (Cell and Tissue Research, 2008)

Field verification of the use of chemical alarm cues in a coral reef fish - M. I. McCormick; J. K. Larson (Coral Reefs, 2007)

Detection of linkage disequilibrium QTLs controlling low-temperature growth and metabolite accumulations in an admixed breeding population of Leymus wildryes - Z.-M. Hu; X.-L. Wu; S. R. Larson; R. R.-C. Wang; T. A. Jones; N. J. Chatterton; A. J. Palazzo (Euphytica, 2005)

MHC class I-like genes in cattle, MHCLA, with similarity to genes encoding NK cell stimulatory ligands - Joshua H. Larson; Mark J. Rebeiz; Chad M. Stiening; Ryan L. Windish; Jonathan E. Beever; Harris A. Lewin (Immunogenetics, 2003)

Evidence for the widespread occurrence of ancient forests on cliffs - D. W. Larson; U. Matthes; J. A. Gerrath; N. W. K. Larson; J. M. Gerrath; J. C. Nekola; G. L. Walker; S. Porembski; A. Charlton (Journal of Biogeography, 2000)
Aim The objective of this work was to determine if the existence of ancient forests on cliffs was specific to the Niagara Escarpment, Canada, or part of a globally widespread pattern. Location Sixty‐five cliff sites were visited in five countries in the temperate climatic zone, and trees were sampled for age and growth rate on forty‐six of these. Methods Two hundred and twenty‐four core samples or cross‐sections were taken from trees on cliffs that varied in height, aspect, rock‐type, and exposure. General observations were also made of regeneration of the tree species forming the mature canopy, and other habitat conditions. Results The evidence shows that ancient slow‐growing forest occurs on most cliffs. Age and growth rate distributions were similar at all treed sites. Small‐statured Thuja, Juniperus , or Taxus stems with age estimates in excess of 1000 years were found in the United States, the United Kingdom and France, and small Pinus and Quercus stems nearly 400 years in Germany. There was a high rate of recurrence of plants in the genera Polypodium , Asplenium , Cystopteris , Campanula , Rosa , Prunus , Hedera , and Sorbus . Most of the sites appear to be habitats of completely natural origin. Conclusions We conclude that ancient natural forest is a normal feature of cliffs, at least in the temperate zone.

Factors influencing the distribution and abundance of diaptomid copepods in high-elevation lakes in the Pacific Northwest, USA - W. J. Liss; G. L. Larson; E. A. Deimling; L. M. Ganio; R. L. Hoffman; G. A. Lomnicky (Hydrobiologia, 1998)

Interaction between Introduced Trout and Larval Salamanders (Ambystoma macrodactylum) in High-Elevation Lakes - Torrey Tyler; William J. Liss; Lisa M. Ganio; Gary L. Larson; Robert Hoffman; Elisabeth Deimling; Gregg Lomnicky (Conservation Biology, 1998)

Interaction between Introduced Trout and Larval Salamanders ( Ambystoma macrodactylum ) in High‐Elevation Lakes - Torrey Tyler; William J. Liss; Lisa M. Ganio; Gary L. Larson; Robert Hoffman; Elisabeth Deimling; Gregg Lomnicky (Conservation Biology, 1998)
The larval stage of the long‐toed salamander (Ambystoma macrodactylum) is the top vertebrate predator in high‐elevation fishless lakes in the North Cascades National Park Service Complex, Washington (U.S.A.). Although most of these high‐elevation lakes were naturally fishless, trout have been stocked in many of them. We sought to determine the effects of physicochemical factors and introduced trout on abundance and behavior of A. macrodactylum larvae. Larval salamander densities were estimated by snorkeling. Snorkelers carefully searched through substrate materials within 2 m of the shoreline and recorded the number of larvae observed and if larvae were hidden in benthic substrates. Physicochemical factors were measured in each lake on the same day that snorkel surveys were conducted. In fishless lakes, larval salamander densities were positively related to total Kjeldahl‐N concentration and negatively related to lake elevation. Crustacean zooplankton, especially cladocerans, were important food resources for larval A. macrodactylum. Crustacean zooplankton and cladoceran densities were positively related to total Kjeldahl‐N, suggesting that increased food resources contributed to increased densities of larval A. macrodactylum. Differences in larval salamander densities between fish and fishless lakes were related to total Kjeldahl‐N concentrations and the reproductive status of trout. Mean larval salamander densities for fishless lakes with total Kjeldahl‐N Interacción entre una Trucha Introducida y Larvas de la Salamandra ( Ambystoma macrodactylum ) en Lagos de Alta Elevación Los estados larvales de la salamandra Ambystoma macrodactylum están entre los depredadores mayores en lagos de alta elevación carentes de peces del North Cascades National Park Service Complex del estado de Washington, en los Estados Unidos. Aunque la mayoría de estos lagos de alta elevación careciéron de peces de manera natural, en varios de ellos se han introducido artificialmente truchas. Nos propusimos determinar los efectos de factores fisico‐químicos y la trucha introducida en la abundancia y conducta de larvas de A. macrodactylum. Las densidades de las larvas fuéron estimadas buceando con snorquel. Los buzos cuidadozemente muestrearon los materiales del substrato dentro de los 2 m a la orilla y anotaron el número de larvas observadas, además de observar si las larvas se encontraban escondidas en substratos bénticos. Los factores fisico‐químicos fueron medidos en cada lago el mismo dia que se realizaron los muestreos de larvas. En lagos sin peces, las densidades de larvas de salamandras se relacionaron positivamente con la concentración total de N‐Kjendahl y negativamente con le elevación del lago. Crustáceos zooplanctónicos, especialmente cladóceros fueron fuentes importantes de recursos para las larvas de A. macrodactylum. Los crustáceos zooplanctónicos y la densidad de cladóceros estuvieron positvamente correlacionados con N‐Kjendahl total, sugiriendo que los incrementos en recursos alimenticios contribuyeron con el incremento en las densidades de larvas. Las diferencias en la densidad de larvas de salamandras entre lago con y sin peces estuvieron relacionadas con las concentraciones de N‐Kjendahl total y el estatus reproductivo de la trucha. La densidad promedio de larvas de salamandras en lagos sin peces con un total de N‐Kjendahl

Structural analysis of glycerol-3-phosphate dehydrogenase from severalDrosophila species - G. K. Chambers; A. A. Felton; J. A. M. Ramshaw; D. Larson Rigby; D. T. Sullivan (Biochemical Genetics, 1985)

Structural analysis of glycerol-3-phosphate dehydrogenase from severalDrosophila species - G. K. Chambers; A. A. Felton; J. A. M. Ramshaw; D. Larson Rigby; D. T. Sullivan (Biochemical Genetics, 1985)

Influence of B and Pl on UDPG:Flavonoid-3-O-glucosyltransferase in Zea mays L. - A. G. M. Gerats; J. Bussard; E. H. Coe; R. Larson (Biochemical Genetics, 1984)

Organic constituents of mutagenic secondary effluents from wastewater treatment plants - David D. Ellis; Cyrenius M. Jone; Richard A. Larson; David J. Schaeffer (Archives of Environmental Contamination and Toxicology, 1982)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)